Exploring the Malaysian law on Halal imported products / Yuhanza Othman … [et al.] - Othman, Yuhanza; Ahmad Mustafa, Mimi Sofiah; Hasan, Zuhairah; Johari, Mohair Nizam (Academy of Contemporary Islamic Studies (ACIS), 2021)
At the end of 2020, Malaysia was slapped with the issue of imported frozen meat from countries not certified halal by Foreign Halal Certification Bodies (FHCB) recognised by the Department of Islamic Development of Malaysia (JAKIM). Regrettably, that was not the first time of such an incidence as there were many cases before that involving misleading halal logos. Indeed, many laws were introduced by the government and JAKIM has taken numerous steps to curtail such an issue from recurring. However, there are still cases reported on the misused of halal logos. Therefore, the first objective of this study is to explore the Malaysian laws, guidelines, and procedures on halal certification for foreign halal logos. In addition to that, the awareness of foreign recognised halal logos is important as a self-protection mechanism to avoid purchasing products with misleading halal logos. Thus, the second objective of this study is to assess the awareness level among consumers toward foreign halal logos attached to imported products marketed in Malaysia. This study is social legal research using content analysis to achieve the first objective and the quantitative method adopted was the descriptive analysis using the Statistical Package for Social Science (SPSS) to achieve the second objective. This study found that the existing laws on the foreign halal logo are comprehensive, but they need support with stringent implementation and enforcement. Also, there is a high level of awareness among respondents toward halal food products but there is less awareness concerning foreign halal logos. Thus, there should be an active awareness campaign regarding foreign halal logos to Malaysians so that self-protection could be enhanced to avoid misleading foreign halal logos.